Omar al‐Hammami: A Case Study in Radicalization. (6th March 2014) - Mastors, Elena; Siers, Rhea; Busch, Kenneth G.; Schouten, Ronald; Weissman, Sidney H.; Felthous, Alan R.
<x xml:space="preserve">Abstract</x> This article presents a case study on the radicalization of Omar al‐Hammami, aka Abu Mansoor al‐Amriki, an American who joined al‐Shabaab, a Somali terrorist group. There are a limited number of in‐depth case studies that help to inform the fragmented discussions in the literature about the radicalization process of Islamic terrorists. Hammami received quite a bit of attention from the government and media due to his "homegrown" status, as well as his prolific use of social media to inform the world of his views and exploits. Hammami did not fully commit to the group, his sense of self‐importance taking precedent over the norms of the group. He left al‐Shabaab, was publicly critical of the group, and was ultimately killed by them. Copyright © 2014 John Wiley & Sons, Ltd.